PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING ANDCOMPOSITION (CIRC)DISERTAI PERMASALAHAN APLIKATIF TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN FISIKA DI SMAN 2 TANGGUL (Studi Pada Materi Kinematika Gerak) - Uvi Sugianti; Albertus Djoko Lesmono; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
The aim of this research is to study the effect of Cooperative Integreted Reading And Composition (CIRC) learning model with application problems through the motivation and the student result in learning physics. In learning, motivation is the most basic things, the absence of motivation mean students do not have a goal in the learning process. This resulted in students will not learn and can not accept and understand the subject matter provided. In the end, success in learning will not be achieved. This experimental researchwas conducted at SMAN 2 Tanggul-Jember. The data are collected through test,questionnaire, interview, and documentation. The examination the hypothesisof this research used independent t-test sample with SPSS 22 version. According to t-test analysis for the motivation of student’s, show that the motivation experiment class is better than the control class. The result of t-test analysis for the student result in learning physics show that the student result of experiment class is better than the control class. The conclusion,the learning model of Cooperative Integreted Reading And Composition (CIRC) with application problems has an significance influential to the motivation and learningresult of physics of student the X-Class in SMAN 2 Tanggul-Jember. Keywords:Cooperative Integreted Reading And Composition (CIRC)Models,Application Problems,Student result, Motivation